ANALISIS SURVIVAL PASIEN PENYAKIT GINJAL KRONIS DENGAN TERAPI PENGGANTI GINJAL DI RUMAH SAKIT PGI CIKINI PERIODE 2015-2020 - Siahaan, Paskalia Clara; Astuti, Putu Ayu Swandewi (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021, 2022)
ABSRACT Chronic Kidney Disease (CKD) has become a public health problem that affects 10-16% of the adult worldwide. The aim of this study was to see the survival and the factors that affect the survival of CKD patients undergoing kidney replacement therapy. The study was an analytic observational study with a hystorical cohort study design. A total of 405 patients were used as a cohort. Data were analyzed using the Life Table method, Kaplan Meier, Log Rank Test, and Cox Regression Test. The mean survival time of CKD patients with renal replacement therapy was 50,7 months. Factors that affected the patients’ survival were albumin levels (HR = 0,499; 95% CI = 0,345-0,846; p = 0,001) and age at first undergoing renal replacement therapy (HR = 1,027; 95% CI = 0,997-1,041); p = 0,009), and the type of health insurance. Comprehensive management of nutritional intake and inflammation is necessary to increase the albumin levels of dialysis patients. Consideration of decision-making for the implementation of renal replacement therapy in elderly patients with CKD need to be done by physicians to increase patient survival. Health education and optimizing the functions of Posbindu PTM can be done as a preventive measure against CKD. Keywords: Survival Analysis, Chronic Kidney Disease, Renal Replacement Therapy